Incorporating CO2 emissions and capacity utilization in the airline inefficiency analysis: A two-stage multiproduct network technology with a nonconvex metafrontier framework - See K.F.; Abdul Rashid A.; Yu M.-M. (Elsevier Ltd, 2025)
In this study, the energy and emissions, as well as the capacity utilization and inefficiencies of global airlines in alliance and nonalliance groups, are analyzed using two-stage multiproduct network technology with a nonconvex metafrontier framework. By integrating group frontier and metafrontier analysis, our proposed model allows us to estimate both the constrained technology and unconstrained capacity gaps among airlines operating with different technologies. We examine the simultaneous effect of capacity utilization, energy and CO2 emissions on global airlines using a metafrontier framework. The empirical results indicate that 12 airlines operate inefficiently at the constrained metafrontier, which may be due to group frontier inefficiency, technology gap inefficiency or both. In terms of network capacity utilization inefficiency, 6 airlines are required to scale labor when operating at maximum capacity. Several strategies are recommended to improve metatechnology technical efficiency and network capacity utilization. ? 2024 Elsevier Ltd